PENGARUH TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP NEGERI 14 PADANG - Kartika, Rica; Rasyid, Yulianti (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this research is three. First, describing the procedure of writing the text of a class VII junior high School 14 Padang before using modelling techniques. Second, describing the procedure of writing the text of Class VII in SMP Negeri 14 Padang after using modeling technique. Third, describing the influence of use of modeling techniques to the skill level of writing the text procedures class VII SMP Negeri 14 Padang. This type of research is quantitative research with experimental methods. This research draft is one group Pretests and posttest design. The population in this study is a grade VII student at SMP Negeri 14 Padang enrolled in Lesson 2018/2019. The samples in this study were determined using purposive sampling techniques. This research variable is the skill of writing the procedure text before and after using the modeling technique of class VII SMP Negeri 14 Padang. This research Data is the test score of the text writing procedure before and after using the modeling technique of class VII SMP Negeri 14 Padang. The Data is analyzed with a percentage formula, average count formula, and test-T. The research instrument is a test of work, which is the test of the text of the procedure before and after using the modeling technique. Kata Kunci: Pengaruh, Teknik Pemodelan, Teks Prosedur